Komunikasi Interpersonal Mahasiswi Perokok Universitas Medan Area - Limbong, Vero Yovita Senitri; Tamsil, Ilma Sakinah (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2025)
The phenomenon of smoking is no longer dominated by men; now, many women, including female students, have become active smokers. However, women smokers are often faced with stronger social stigma and negative judgment. This condition makes this research interesting to examine the way women smokers communicate to build their existence and face their environment. The purpose of this study is to analyze the interpersonal communication of female smokers communicating with others in the Medan Area University (UMA) environment. This study also looks at how they build self-identity and negotiate meaning in an effort to overcome social stigma. To understand the experiences of the five informants, this study used a phenomenological qualitative approach. In-depth interviews and observations were used to collect data. The theory used in this study utilizes Interpersonal Needs Theory. The results showed that female smokers among female students of Medan Area University are already a trend, this is already a culture for them, but it's just that other women who are not smokers still feel not too good if women smoke. Interpersonal needs theory explains how basic individual needs affect communication. In conclusion, the interpersonal communication of women smokers is not only a means of interaction, but also an adaptation strategy to the social stigma in the academic environment.